1988
DOI: 10.1002/ajh.2830290412
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology and special clinical applications of low‐molecular‐weight heparins

Abstract: In this overview, the rationale of the development of low-molecular-weight (LMW) heparins and their toxicological, anticoagulant, fibrinolytic, lipolytic, and protamine interactions are summarized. Clinical experiences are reviewed on the benefit of LMW heparin for anticoagulation in patients with bleeding and other complications on conventional anticoagulants and during pregnancy. It is concluded that animal experiments have demonstrated the safety of LMW heparins, that the pharmacologic profile is improved c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

1990
1990
2001
2001

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 103 publications
0
11
1
Order By: Relevance
“…Previous studies with LMWHs have shown that the APTT inhibition test remains essentially unaffected during therapy with LMWH [20,22]. In contrast, our study indi cates a modest but statistically significant ef fect of dalteparin regarding the APTT value.…”
Section: Discussioncontrasting
confidence: 75%
“…Previous studies with LMWHs have shown that the APTT inhibition test remains essentially unaffected during therapy with LMWH [20,22]. In contrast, our study indi cates a modest but statistically significant ef fect of dalteparin regarding the APTT value.…”
Section: Discussioncontrasting
confidence: 75%
“… 2 They are considered to be as effective an anticoagulant as unfractionated heparin and to have better pharmacodynamic and pharmacokinetic profiles. Clinical data suggest that low‐ molecular‐weight heparins are safer than unfractionated heparin 3 . It was recently found that, like unfractionated heparin, low‐molecular‐weight heparins possess anti‐inflammatory properties, independent of their anticoagulant properties 4 , .…”
Section: Introductionmentioning
confidence: 99%
“…Conse quently, the placental transport of each LMM heparin has to be investigated separately. These investigations are of importance for performing long-term prophylaxis of throm boembolism during pregnancy [22,23,[29][30][31]. Accordingly, the LMM heparin described in the present report can be used to set up a controlled prospective trial in a larger outpa tient setting for prophylaxis of thromboembo lism in pregnancy.…”
Section: Discussionmentioning
confidence: 98%